The Effect of Advertising on Brand Image: A Consumers Perspective - Rupani, Puja (2006)
Advertising is a primary tool for communication with the public. With increasing competition, advertising aims to reach its target consumers creating an brand image. Companies can position themselves in particular market, to covey their position advertising is a good medium. Consumers are influenced by many psychological, social and personal factors that influence their perception of advertisements. This study examines how advertising effects brand image from a consumers perspective. The findings suggest that the consumers in UK are cynical about advertisements but still consider it an important medium in conveying information about the products, brands and companies.